2003
DOI: 10.1016/s0005-2736(03)00028-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular characteristics of system l in human breast cancer cells

Abstract: The functional and molecular properties of system L in human mammary cancer cells (MDA-MB-231 and MCF-7) have been examined. All transport experiments were conducted under Na(+)-free conditions. alpha-Aminoisobutyric acid (AIB) uptake by MDA-MB-231 and MCF-7 cells was almost abolished by BCH (2-amino-2-norbornane-carboxylic acid). AIB uptake by MDA-MB-231 cells was also inhibited by L-alanine (83.6%), L-lysine (75.6%) but not by L-proline. Similarly, L-lysine and L-alanine, respectively, reduced AIB influx int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…In our study, we observed that 94% of breast tumor tissues are LAT1 positive. Previous investigations have shown that LAT1 is not detectable in normal breast tissues [17]. Our results demonstrated that the normal breast tissues adjacent to the tumor site expressed a low intensity of LAT1.…”
Section: Efficient Detection Of Breast Tumors By Anti-[ 18 F]facbc-petsupporting
confidence: 49%
See 1 more Smart Citation
“…In our study, we observed that 94% of breast tumor tissues are LAT1 positive. Previous investigations have shown that LAT1 is not detectable in normal breast tissues [17]. Our results demonstrated that the normal breast tissues adjacent to the tumor site expressed a low intensity of LAT1.…”
Section: Efficient Detection Of Breast Tumors By Anti-[ 18 F]facbc-petsupporting
confidence: 49%
“…Actively proliferating cancer cells require more nutrients, such as amino acids and glucose, than quiescent cells. With regard to the relationship between LAT1 and breast cancer, there have been only four publications so far reporting the role of LAT1 in two cultured breast cancer cell lines, from Shennan and his colleagues [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Many tumors express CD98hc, and its expression correlates with poor prognosis in B cell lymphomas (Holte et al, 1987;Holte et al, 1989;Salter et al, 1989). Furthermore, nearly all studies that have examined the expression of CD98hc or CD98 light chains in solid tumors show that their expression is correlated with progressive or metastatic tumors (Esteban et al, 1990;Kaira et al, 2009a;Kaira et al, 2009b;Kaira et al, 2009c;Kaira et al, 2008;Kaira et al, 2009d;Kobayashi et al, 2008;Nawashiro et al, 2002;Nawashiro et al, 2006;Oleinik et al, 2005;Powlesland et al, 2009;Shennan et al, 2003;Xiao et al, 2005).…”
Section: Cd98 Expression In Tumorsmentioning
confidence: 99%
“…High LAT1 expression correlates with poor survival; LAT1 inhibition decreases glioma tumor cell growth (Nawashiro et al, 2006) Breast cancer cell lines LAT-1 inhibitors suppress tumor cell growth and metabolism (Shennan and Thomson, 2008;Shennan et al, 2003) (Mouse) Embryonic stem cell teratomas Genetic deletion of CD98hc blocks tumor growth (Feral et al, 2005) Blood proteins during lung cancer High soluble CD98 and two other blood proteins may be a tumor biomarker (Xiao et al, 2005) Breast tissue RNA Expression of CD98-encoding mRNAs correlates with poor prognosis (Esseghir et al, 2006) Multiple CD98hc and LAT-1 expression is higher in metastatic than primary tumor sites (Kaira et al, 2008) (Mouse) Glioma cells Overexpression of CD98 light chain LAT-1 enhances tumor growth rate in vivo (Kobayashi et al, 2008) Pulmonary tumors CD98 expression predicts poor prognosis (Kaira et al, 2009a;Kaira et al, 2009b;Kaira et al, 2009c) Renal cell cancer CD98 histological expression correlates directly with malignancy grade (Prager et al, 2009) Squamous cell carcinoma lines CD98 light chain LAT-1 inhibitor improves efficacy of cisplatin treatment (Yamauchi et al, 2009) Non-small cell lung cancer LAT-1 inhibitor BCH reduces viability of tumor cells ex vivo (Imai et al, 2010) Chicken cell line and HeLa cells Genetic disruption or inhibition of LAT-1 blocks tumor cell growth in vitro and in vivo (Ohkawa et al, 2011) allowing a cell to exert force on the ECM through integrin-driven RhoA signaling , which is a key element in the sensing of stiffness (Samuel et al, 2011). Anchorage independence (i.e.…”
Section: Cd98 Integrin Signaling Function In Cancermentioning
confidence: 99%
“…This suggests that IDO-mediated depletion of cellular tryptophan pools is very efficient also in vivo. Moreover, many cells lack high-affinity tryptophan import systems and are in turn predominantly, if not exclusively, dependent on the neutral amino acid transporter system L for import of tryptophan (25,31,32). However, considering the relatively low substrate affinity in combination with the extensive substrate promiscuity of this permease, tryptophan uptake would be greatly reduced at very low exogenous concentrations as other amino acids compete for transport (24,31).…”
mentioning
confidence: 99%